Human airway smooth muscle maintain in situ cell orientation and phenotype when cultured on aligned electrospun scaffolds - Morris, G E; Bridge, J C; Eltboli, O M I; Lewis, M P; Knox, A J; Aylott, J W; Brightling, C E; Ghaemmaghami, A M; Rose, F R A J (American journal of physiology. Lung cellular and molecular physiology, 2014)
Human airway smooth muscle (HASM) contraction plays a central role in regulating airway resistance in both healthy and asthmatic bronchioles. In vitro studies that investigate the intricate mechanisms that regulate this contractile process are predominantly conducted on tissue culture plastic, a rigid, 2D geometry, unlike the 3D microenvironment smooth muscle cells are exposed to in situ. It is increasingly apparent that cellular characteristics and responses are altered between cells cultured on 2D substrates compared with 3D topographies. Electrospinning is an attractive method to produce 3D topographies for cell culturing as the fibers produced have dimensions within the nanometer range, similar to cells' natural environment. We have developed an electrospun scaffold using the nondegradable, nontoxic, polymer polyethylene terephthalate (PET) composed of uniaxially orientated nanofibers and have evaluated this topography's effect on HASM cell adhesion, alignment, and morphology. The fibers orientation provided contact guidance enabling the formation of fully aligned sheets of smooth muscle. Moreover, smooth muscle cells cultured on the scaffold present an elongated cell phenotype with altered contractile protein levels and distribution. HASM cells cultured on this scaffold responded to the bronchoconstrictor bradykinin. The platform presented provides a novel in vitro model that promotes airway smooth muscle cell development toward a more in vivo-like phenotype while providing topological cues to ensure full cell alignment.